2018
DOI: 10.1007/s00127-018-1565-3
|View full text |Cite
|
Sign up to set email alerts
|

A NEET distinction: youths not in employment, education or training follow different pathways to illness and care in psychosis

Abstract: PurposeThe early phases of psychosis, including the prodrome, often feature educational/occupational difficulties and various symptoms and signs, that can render or keep youths “Not in Employment, Education or Training” (NEET). Conversely, NEET status itself may increase risk for illness progression and impaired functioning, and impede access to appropriate services for psychosis. As these issues have not been investigated, we aimed to examine differences in the illness and care pathways and characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 49 publications
4
29
0
1
Order By: Relevance
“…Comparisons to previous literature are complicated by the lack of studies using psychometric measures of social inclusion to examine group differences between young adults from the general community and those with SMI. Nonetheless, these findings are consistent with evidence that young adults with SMI have smaller social networks (Gayer-Anderson & Morgan, 2013), are less vocationally engaged (Iyer et al, 2018), experience lower levels of independence (Breitborde, Woolverton, Frost, & Kiewel, 2014) and higher levels of housing instability (Narendorf, Cross, Santa Maria, Swank, & Bordnick, 2017) than those from the general community.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Comparisons to previous literature are complicated by the lack of studies using psychometric measures of social inclusion to examine group differences between young adults from the general community and those with SMI. Nonetheless, these findings are consistent with evidence that young adults with SMI have smaller social networks (Gayer-Anderson & Morgan, 2013), are less vocationally engaged (Iyer et al, 2018), experience lower levels of independence (Breitborde, Woolverton, Frost, & Kiewel, 2014) and higher levels of housing instability (Narendorf, Cross, Santa Maria, Swank, & Bordnick, 2017) than those from the general community.…”
Section: Discussionsupporting
confidence: 83%
“…Young adults with SMI are considered socially excluded (Social Exclusion Unit, 2005). This is largely based on evidence from objective indicators, for example, lower vocational engagement relative to peers from the general community (Iyer et al, 2018). However, subjective indicators are under-researched in this population (Sündermann, Onwumere, Bebbington, & Kuipers, 2013), where loneliness remains poorly understood (Lim, Gleeson, Alvarez-Jimenez, & Penn, 2018).…”
mentioning
confidence: 99%
“…The major psychoses (ie, schizophrenia spectrum and bipolar I disorder) are recognized as a leading cause of disability worldwide [1] and are associated with poverty [2], premature mortality [3], impaired cognitive function [4], loss of education and employment [5], and increased global economic burden [6]. Published practice guidelines outlining the usual treatment for psychosis identify antipsychotic medication as a frontline treatment for positive symptom management and adjunct psychosocial interventions such as psychoeducation, family support, vocational interventions, and cognitive behavioral skills-based therapies [7][8][9][10][11].…”
Section: Psychosis and Engagementmentioning
confidence: 99%
“…The Nordic countries have been characterized by relatively low NEET rates, the highest rates occurring in the southern regions of Europe [13][14][15][16]. In several studies, NEETs have been identified as at high risk for adverse economic, health, and psychosocial outcomes [17][18][19]. The mean proportion of young persons classified as NEETs was in OECD 14.3% for persons aged 18-to 24 [16].…”
Section: Agency Of Young Adults Who Are Not In Education Employment or Trainingmentioning
confidence: 99%